Review of Cross-Leg Flaps in Reconstruction of Posttraumatic Lower Extremity Wounds in a Microsurgical Unit - Mahajan, Ravi K.; Srinivasan, Krishnan; Ghildiyal, Harish; Singh, Mahipal; Jain, Adish; Kapadia, Taha; Tambotra, Ankush (Indian Journal of Plastic Surgery, 2019)
Since the advent of microsurgery, and expanding expertise in the field, extensive traumatic wounds of leg have been managed successfully with free tissue transfer. Various patient-related factors may preclude the use of free flaps even in units with available expertise and infrastructure. It is in such situations that the “cross-leg flap” comes into play. In these cases, instead of attempting complicated anastomotic techniques or anastomosis in the zone of trauma, it is better to perform the simpler and more reliable cross-leg flap. In this study, we try to show the utility of a cross-leg flap based on a retrospective study of 198 patients who underwent cross-leg flap in our institute over a period of 15 years extending from November 2003 to March 2018. Materials and methods: Case sheets of all patients who underwent cross-leg flap from November 2003 to March 2018 were reviewed. The location of defect in the leg, the indication for cross-leg flap, the pattern of cross-leg flap, and perioperative complications were noted. Results: A total of 198 patients underwent cross-leg flap for traumatic soft tissue injury of leg during this period. The most common reason for performing cross-leg flap was poor pulsatility of the recipient artery as seen intraoperatively, followed by the economics of the procedure wherein the initial cost of free flap was found significantly higher compared with cross-leg flap. All flaps survived with partial necrosis occurring in 23 patients. All flaps settled well by 2 years’ time. Bony union/fracture healing evaluation was not a part of this study. Conclusion: Cross-leg flap is still a useful tool for leg wound coverage even in microsurgical unit in situations precluding free flap coverage.
Keywords: cross leg flap; leg defect; free flap